EVALUASI KINERJA PELAYANAN PUBLIK DALAM PROSES PEMBUATAN PASPOR DI UNIT KANTOR KEIMIGRASIAN (UKK) KOTA PROBOLINGGO - Al-Halim, Achmad Rifqi; N, Veronica Astuti; Puspitarini, Renny Candradewi (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2025)
The research aims to analyze and evaluate the operational performance of the passport issuance service system at the Probolinggo City Immigration Work Unit. This study employs a qualitative research methodology, involving 100 informants selected to represent various stakeholders interacting with the service system. Data collection methods include in-depth interviews, direct field observations, and comprehensive documentary studies, providing a holistic perspective on the operational aspects of the service. The collected data were processed and analyzed using an interactive analysis method to identify patterns, strengths, and areas for improvement in service delivery. The findings reveal that the operational performance of the passport issuance service system is generally satisfactory, with several indicators pointing to a high level of efficiency and effectiveness. Key factors contributing to this positive evaluation include streamlined processes, responsive staff, and a well-maintained infrastructure that supports smooth operations. Furthermore, the research highlights the system's capacity to handle varying levels of demand without compromising service quality, demonstrating its robustness and adaptability. However, the study also identifies opportunities for enhancement, particularly in integrating digital technologies to further improve accessibility and reduce waiting times for applicants. Based on the evidence gathered, the research concludes that the Probolinggo City Immigration Work Unit's passport service system operates at a good level, with certain aspects performing at an excellent standard. These findings provide valuable insights for policymakers and practitioners aiming to replicate or improve similar systems in other regions